EU organic logo and its perception by consumers. Issue 5 (5th May 2015) - Zander, Katrin; Padel, Susanne; Zanoli, Raffaele
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – With the introduction of the mandatory European Union (EU) organic logo for all organic food products in 2010, the European Commission aimed at fostering the internal organic food market. This needs consumers' knowledge of the logo. According to earlier research consumers' knowledge of the EU organic logo is low. Thus, the purpose of this paper is to elicit consumers' attitudes towards organic certification and labelling and to develop recommendations on how to improve consumers' knowledge of the EU organic logo. Design/methodology/approach – By means of an online survey with 3, 000 participants in six European countries, knowledge of the logo and attitudes towards organic farming and European labelling, as well as organic food purchase behaviour and socio-demographic indicators were elicited. Factor and cluster analysis based on several statements on the test persons' attitudes towards organic farming and corresponding EU legislation were conducted in order to segment consumers. Findings – The results indicate that knowledge of the logo is low. Only about 15 per cent of all respondents knew its meaning. Four clusters of consumers could be identified: "Committed organics", "Pragmatic organics", "Organic sceptics" and Organic disinteresteds'. With reference to the EU organic legislation's aim of promoting the organic market, particularly "Organic sceptics" should be addressed by emphasising the trustworthiness of the organic certification and labelling system. Originality/value – Segmenting consumers according to their attitude towards organic farming, its labelling and certification allows for targeted and efficient communication and organic market development.